Peran Keluarga dalam Pembentukan Identitas dan Kesejahteraan Psikologis Karyawan di CV. SUGIH MAJU BERKAH - Ageng Saepudin Kanda S; Fika Anilda (MAMEN: Jurnal Manajemen, 2024)
This research aims to reveal the role of family in the formation of identity and psychological well-being of employees at CV. SUGIH FORWARD BLESSINGS. Employee identity and psychological well-being are important aspects in supporting productivity and performance in the work environment. Using a qualitative approach, this research involved in-depth interviews with a number of CV employees. SUGIH MAJU BERKAH to explore how their family experiences influence individual identity and psychological well-being in the work context. The research results show that the family plays a crucial role in shaping employee identity, through the influence of the values, norms and emotional support provided. Interactions with family members also play a role in shaping employees' mindsets and attitudes towards their work. In addition, family support has a positive impact on psychological well-being, creating an emotionally healthy work environment and increasing employees' mental resilience. These findings provide an important contribution to understanding the role of the family in the context of identity formation and psychological well-being of employees in the CV work environment. SUGIH MAJU BERKAH, as well as providing suggestions for developing human resource management strategies that are more holistic and oriented towards family support to improve employee psychological well-being.